Hygienic value of water - Wagner, Jessie May (My University, 1900)
Introduction: Since water is such a common compound and occurs almost everywhere in nature in some form, but few people realize its value both as to hygiene and its use in maintaining health and life. In all cases of disease, it is the duty of the physician to restore the patient to health by the simplest means in his power. Water is least expensive, but this does not need to lower one’s estimation of its value. It is also a simple means to use in restoring health. Prof. W. Parker says, “Hygiene is of far more value in treatment of disease than drugs.” In order to understand the relation of water to the system, we must first become acquainted with its physical properties and all other facts relating to it.
Citation: Wagner, Jessie May. Hygienic value of water. Senior thesis, Kansas State Agricultural College, 1900.
Morse Department of Special Collections
Keywords: Water; Medical Use of Water; Theses; Manuscripts (documents)